Analisis perhitungan dan pencatatan penerimaan Bea Perolehan Hak atas Tanah dan Bangunan di Badan Pendapatan Daerah Kabupaten Minahasa - Tampi, Mercy Christiani; Elim, Inggriani; Wangkar, Anneke (Yayasan Widyantara Nawasena Raharja, 2024)
Land and Building Acquisition Fee (or BPHTB) is an important source of regional income to support development in Minahasa Regency. This research aims 1) To find out the calculation of fees for acquiring land and building rights at the Regency Regional Revenue Agency Minahasa. 2) To find out the system for recording fees for acquiring rights to land and buildings at the Regency Regional Revenue Agency Minahasa. The data analysis method used in this research is the descriptive analysis method with data collection methods, namely interviews and documentation. The research results show that the calculation of BPHTB is carried out after the NPOP is determined as the basis for taxation minus the Non-Taxable Tax Object Acquisition Value (NPOPTKP) of IDR 60,000,000 for each taxpayer and IDR 300,000,000 for rights due to inheritance or testamentary grants. Then multiplied by a rate of 5%. The calculation has been carried out in accordance with the regulations, namely Minahasa Regency Regional Regulation Number 2 of 2011 concerning Land and Building Acquisition Fees. Recording of BPHTB receipts is adjusted to the taxes received and recording is carried out through proof of deposit, which can be in the form of a Deposit Certificate (SKS) from a bank or bank statement, all payment data is then inputted into the application system digitally. The BPHTB transaction or receipt recording system uses the BPHTB application system which is integrated with the land registration service system by the National Land Agency (or BPN).